2022
DOI: 10.1088/1475-7516/2022/10/003
|View full text |Cite
|
Sign up to set email alerts
|

Exploring physical properties of minimally deformed strange star model and constraints on maximum mass limit in f(š’¬) gravity

Abstract: Our current investigation is inherently linked to the observations of gravitational waves from the GW190814 event which suggests that the source of the signals can be ascribed to a compact binary coalescence of a 22.2 to 24.3M āŠ™ black hole and a compact object endowed with a mass of 2.50 to 2.67M āŠ™. In the current exposition, we are concerned with modeling of the lower mass component of the coalescence pair. We utilize the f(š’¬) gravity together with the Minimal Geometric De… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 129 publications
(139 reference statements)
0
5
0
Order By: Relevance
“…[ 76 ] Recently, the physical properties of strange star model using MGD and extended MGD approaches along with constraints on maximum mass limit under ffalse(scriptQfalse)$f(\mathcal {Q})$ gravity have been investigated by Maurya et al. [ 78,79 ] Hassan et al. [ 80 ] explored the wormhole solutions first time in the background of symmetric teleparallel ffalse(Qfalse)$f(Q)$ gravity.…”
Section: Introductionmentioning
confidence: 99%
“…[ 76 ] Recently, the physical properties of strange star model using MGD and extended MGD approaches along with constraints on maximum mass limit under ffalse(scriptQfalse)$f(\mathcal {Q})$ gravity have been investigated by Maurya et al. [ 78,79 ] Hassan et al. [ 80 ] explored the wormhole solutions first time in the background of symmetric teleparallel ffalse(Qfalse)$f(Q)$ gravity.…”
Section: Introductionmentioning
confidence: 99%
“…They found that negative values of the model parameters support to more stellar masses while positive values reduce the amount of matter of the star. Maurya et al [54] used minimum geometric deformation technique to obtain compact stellar objects with masses aligned with the GW190814 event in f (Q) gravity. They showed that metricity parameter and deformation constant play a crucial role in determining the viability and stability of compact stellar models.…”
Section: Introductionmentioning
confidence: 99%
“…The bouncing Universe model is also studied in f (Q) gravity [30]. Several other models along with wormhole geometries are also investigated in f (Q) gravity theory [31][32][33][34][35][36][37][38]. In this article, the f (Q) gravity will be used to obtain a solution of field equations for compact stars.…”
Section: Introductionmentioning
confidence: 99%